Exponent Rules
posted by Anonymous on .
SAC = STC/y = (w1(y/240)^2 + 48w2) / y
= (w1)(y/240)^2(y) + ((48)(w2))/y
= (w1)(y/240)^2 + ((48)(w2))/y < this is the final answer, but I don't understand it because of this part:
(w1)(y/240)^2(y) > (w1)(y/240)^2
Don't you add exponents when you multiply variables? So wouldn't it become...
(w1)(y^3/240^2)??
Note: w1, y, w2 are variables

well, you can add, but remember this
1/y= y^{1} 
(y^2/240^2)/y
(y^2/240^2)(y/1)
y^3/240^2???
I don't get how y^1 is relevant to this question since (x/y)/z can be rearranged as (x/y)(z/1)..